2021
DOI: 10.3390/nu13062089
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Human Milk Feeding and Short-Term Growth in Preterm and Very Low Birth Weight Infants

Abstract: Human milk (HM) is the gold standard for feeding infants but has been associated with slower growth in preterm infants compared with preterm formula. This systematic review and meta-analysis summarises the post-1990 literature to examine the effect of HM feeding on growth during the neonatal admission of preterm infants with birth weight ≤1500 g and/or born ≤28 weeks’ gestation. Medline, PubMed, CINAHL, and Scopus were searched, and comparisons were grouped as exclusive human milk (EHM) vs. exclusive preterm f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
(383 reference statements)
1
3
0
Order By: Relevance
“…There was no difference in head circumference growth, regardless of whether the human milk was fortified. Similar results were found in the SR conducted by Suganuma et al in 2021, in which there was no significant association between short-term growth outcomes with feeding type (7). The authors reported insufficient evidence to determine effects on any outcomes.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…There was no difference in head circumference growth, regardless of whether the human milk was fortified. Similar results were found in the SR conducted by Suganuma et al in 2021, in which there was no significant association between short-term growth outcomes with feeding type (7). The authors reported insufficient evidence to determine effects on any outcomes.…”
Section: Discussionsupporting
confidence: 76%
“…SRs have been conducted on the outcomes after human milk intake in VLBW infants (7,8). Miller et al conducted an SR in 2018 to evaluate the association between human milk feeding and morbidity, and Saguna conducted an SR in 2021 on the association between human milk feeding and short-term growth in VLBW preterm infants (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After discharge and with a close monitoring of growth in PT SGA, EBF until 6 months can be advised with the aim to achieve a catch up with a slow and progressive weight gain without any rapid acceleration exposing to the obesity and others diseases in adulthood. Although in a recent systematic review, involving over 10,000 VLBW infants, we have found much of the evidence for the association between growth outcomes and HM intake to be inconclusive, largely due to the quality of the evidence [13].…”
Section: Nutrition Of Pt Sga In the First Months Of Lifementioning
confidence: 78%